Physical Activity across Frailty Phenotypes in Females with Parkinson’s Disease - Kaitlyn P. Roland; Kayla M. D. Cornett; Olga Theou; Jennifer M. Jakobi; Gareth R. Jones (Journal of Aging Research)
Females with Parkinson’s disease (PD) are vulnerable to frailty. PD eventually leads to decreased physical activity, an indicator of frailty. We speculate PD results in frailty through reduced physical activity. Objective. Determine the contribution of physical activity on frailty in PD (n=15, 65 ± 9 years) and non-PD (n=15, 73 ± 14 years) females. Methods. Frailty phenotype (nonfrail/prefrail/frail) was categorized and 8 hours of physical activity was measured using accelerometer, global positioning system, and self-report. Two-way ANCOVA (age as covariate) was used to compare physical activity between disease and frailty phenotypes. Spearman correlation assessed relationships, and linear regression determined associations with frailty. Results. Nonfrail recorded more physical activity (intensity, counts, self-report) compared with frail. Self-reported physical activity was greater in PD than non-PD. In non-PD, step counts, light physical activity time, sedentary time, and self-reported physical activity were related to frailty (R=0.91). In PD, only carbidopa-levodopa dose was related to frailty (r=0.61). Conclusion. Physical activity influences frailty in females without PD. In PD females, disease management may be a better indicator of frailty than physical activity. Further investigation into how PD associated factors contribute to frailty is warranted.